2014
DOI: 10.1038/ncomms6641
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput detection of miRNAs and gene-specific mRNA at the single-cell level by flow cytometry

Abstract: Fluorescent in situ hybridization (FISH) is a method that uses fluorescent probes to detect specific nucleic acid sequences at the single cell level. Here we describe optimized protocols that exploit a highly sensitive FISH method based on branched DNA technology to detect mRNA and miRNA in human leukocytes. This technique can be multiplexed and combined with fluorescent antibody protein staining to addressa variety of questions in heterogeneous cell populations. We demonstrate antigen-specific upregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 27 publications
2
130
0
Order By: Relevance
“…For this purpose, we used a recently described (21) and cuttingedge technique (Flow-FISH) for miR-210 detection along with anti-Gr1 þ and anti-CD11b þ antibodies by flow cytometry directly on splenic and tumor-infiltrating MDSCs. We found that the percentage of miR-210-expressing positive cells was significantly higher on tumor-infiltrating MDSCs as compared with splenic MDSC in both B16-F10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we used a recently described (21) and cuttingedge technique (Flow-FISH) for miR-210 detection along with anti-Gr1 þ and anti-CD11b þ antibodies by flow cytometry directly on splenic and tumor-infiltrating MDSCs. We found that the percentage of miR-210-expressing positive cells was significantly higher on tumor-infiltrating MDSCs as compared with splenic MDSC in both B16-F10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SIV detection in rhesus macaques). This type of mRNA Flow-FISH assay can also be used to detect cytokines 24 , host factors and/or other pathogen related RNAs. Lastly, the assay could be transferred to alternative cell types; the protocol here focuses on the CD4 T cell reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Highly specific and sensitive hybridization probes enable the detection of target nucleic acids without the need for additional enzymes and at previously unachievable single-molecule resolution [14]. Unlike PCR, such probes amplify only the signal and not the target, and unlike enzyme-linked reagents they only involve restriction enzymes.…”
Section: Enzyme-free Hybridization Assays: Specificity In Focusmentioning
confidence: 99%
“…Unlike PCR, such probes amplify only the signal and not the target, and unlike enzyme-linked reagents they only involve restriction enzymes. Over the past couple decades, hybridization probes have become a fundamental aspect of widely applied techniques such as fluorescence in situ hybridization (FISH), flow cytometry, and fluorescence microscopy [14][15][16]. Among other approaches for enzyme-free signal-enhancement we distinguish two major strategies: branched DNA (bDNA) or sequence amplification through cascade hybridization, and signal-enhancing by laser microscopy.…”
Section: Enzyme-free Hybridization Assays: Specificity In Focusmentioning
confidence: 99%